Smart people should build things : how to restore our culture of achievement, build a path for entrepreneurs, and create new jobs in America - Yang, Andrew (Entrepreneur) (Harper Business, an imprint of HarperCollins Publishers, 2014)
The founder and CEO of Venture for America steers young graduates toward entrepreneurship, interweaving success stories with explanations of why current trends are leading to economic distress and cultural decline.